Penyelesaian Sengketa Penanaman Modal Asing yang Melibatkan Badan Pemerintahan atau Institusi Indonesia Melalui Arbitrase - Monica Septyana, Farah (Universitas Ekasakti, 2023)
Globalization makes the non-physical boundaries between countries borderless. This condition opens the opportunity for foreign investment from one country to another. The proliferation of foreign investments in Indonesia has ignited a growing number of disputes between foreign investors and the Indonesian investors, the Indonesian government or related institutions. This study aims to learn more about the types of foreign investment dispute resolution in Indonesia, starting from deliberation to reach consensus, Alternative Dispute Resolution, litigation, and especially Arbitration which are the most widely used dispute settlement in Indonesia. This research is a normative legal research conducted using a normative juridical approach. Regarding foreign investment dispute settlement, foreign investors tend to avoid litigation and prefer settlement through arbitration. The position of arbitration as an investment dispute settlement is getting stronger with the existence of special arbitration institutions such as ICSID, UNCITRAL, and BANI, even more so with the recognition of international arbitral bodies or boards’s decisions which can be executed in other countries of the same ratification participants.